Journal of Geophysical Research: Planets - Journal of Geophysical Research: Planets (Wiley, 2026)
The Journal of Geophysical Research: Planets is dedicated to the publication of new and original research in the broad field of planetary science. Manuscripts concerning planetary geology, geophysics, geochemistry, atmospheres, and dynamics are appropriate for the journal when they increase knowledge about the processes that affect Solar System objects. Manuscripts concerning other planetary systems, exoplanets or Earth are welcome when presented in a comparative planetology perspective. Studies in the field of astrobiology will be considered when they have immediate consequences for the interpretation of planetary data. JGR: Planets does not publish manuscripts that deal exclusively with future missions and instrumentation, nor those that are primarily of an engineering interest, unless they present a current planetary application. Instrument, calibration, theory/modeling or data processing papers may be appropriate for the journal, but only when accompanied by scientific analysis and interpretation that increases understanding of the studied object. A manuscript that describes a new method or technique would be acceptable for JGR: Planets if it contained new and relevant scientific results obtained using the method.
FI 1.26
Q1
Keywords: Earth; Space & Environmental Sciences; Space and Planetary Sciences; Acuerdos transformativos; Transformative agreements; Ciencia planetaria; Geofísica planetaria; Geología planetaria; Geoquímica; Atmósferas planetarias; Dinámica planetaria